Some new `Short Games` within a set of tennis - Pollard, G.; Barnett, T. (International Journal of Computer Science in Sport, 2018)
Recently there has been an interest in developing tennis scoring systems that involve playing a fewer number of points on average. In devising such `shorter` tennis scoring systems, it would be ideal for them to also have the following four characteristics: A smaller standard deviation of duration, a similar value for the probability that the better player wins, an increased efficiency, and a greater average excitement per point played. Thus, in total there are five considerations when devising such new scoring systems. Quite often in this type of study a scoring system that is `better` with regard to one of these characteristics is `worse` with regard to another (or others). In this paper we outline some new tennis scoring systems that have improvements in all (or almost all) of these five characteristics. We identify 3 or 4 different game structures that could be useful for tournaments. A common thread in the approach taken is the elimination of unimportant and unexciting points within the game structure. The choice of which is the most appropriate new format for a particular tournament would depend amongst other things on the planned reduction in the expected set duration.